2011
DOI: 10.1016/j.spinee.2011.07.026
|View full text |Cite
|
Sign up to set email alerts
|

“Spring-back” closure associated with open-door cervical laminoplasty

Abstract: Spring-back closure occurred in 10% of our patients at or before 6 months after surgery. The incidence of spring-back by level (ie, 117 laminae) was 6%, mainly occurring at the lower cervical spine. All spring-back closures were partial segmental closures, most commonly involving C5 and C6. Postoperative neurologic deficit was associated with spring-back closure; therefore, surgeons should adopt preemptive surgical measures to prevent the occurrence of such a complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…56 Age (n = 3) 51,56,68 and sex (n = 3) 51,56,68 were not significant predictors of surgical complications.…”
Section: 42mentioning
confidence: 92%
See 1 more Smart Citation
“…56 Age (n = 3) 51,56,68 and sex (n = 3) 51,56,68 were not significant predictors of surgical complications.…”
Section: 42mentioning
confidence: 92%
“…Twenty-seven additional papers reported on predictors of complications but did not use an adequate multivariate statistical analysis. The following is a summary of the primary outcomes of these studies: postoperative complications (n = 4); 20,27,50,52 nerve root palsy (n = 8); [7][8][9]12,31,42,49,53 radiculopathy (n = 3); 24,40,67 shoulder stiffness and neck pain (n = 1); 76 instability (n = 1); 25 postoperative kyphosis (n = 2); 34,64 axial pain (n = 3); 54,55,61 pseudarthrosis (n = 1); 16 graft dislodgement (n = 2); 16,45 closure of lamina (n = 2); 51,68 and reconstruction failure (n = 1). 56 For KQ2, a total of 28 therapeutic cohort studies (2 randomized control trials, 11 prospective, 15 retrospective) met our inclusion criteria.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The incidence of reclosure of opened laminae is 1.5-10% in some studies. 4,7,14,31,34 Matsumoto et al reported a rate of 34% for lamina closure in their patients. 15 Closure of the lamina are typically seen after one to three months following surgery.…”
Section: Discussionmentioning
confidence: 93%
“…Kandziora et al compared the anatomic, radiographic, computerized tomographic, and biomechanical data of human and sheep cervical spines; their findings indicate a good comparability and encouraged the use of the sheep cervical vertebrae as a model for human cervical spine research. [21][22][23][24][25][26][27][28][29][30][31][32][33] The use of animal models also have some disadvantages including differences in anatomy, size, and kinematics compared with humans; however, animal models offer the advantages of good homogeneity (in terms of age, weight, and gender), availability, and similarities to humans. Additionally, the uncovertebral joints of the cervical spine in humans are not available in sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation